2018
DOI: 10.21273/hortsci13065-18
|View full text |Cite
|
Sign up to set email alerts
|

Ebb-and-flow Subirrigation Strategies Increase Biomass and Nutrient Contents and Reduce Nitrate Levels in Lettuce

Abstract: Overhead irrigation is widely used to water lettuce during commercial production in China but exerts potential water wastage and pollution. Subirrigation is thought as a water-saving, high-efficiency fertigation strategy. However, few studies have compared the nutritional value and nitrate content of lettuce grown using subirrigation with plants cultivated with overhead irrigation. Therefore, this study explored the ability of ebb-and-flow subirrigation strategies to produce high yields of a leafy lett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Plug trays filled with substrate is used for greenhouse baby leaf production with ebb-and-flow (E&F) irrigation systems (Danfeng et al, 2013). E&F irrigation is characterized as producing uniform plants, with a short production cycle, high water-and fertilizer-use efficiency, and adequate plant quality (Yang et al, 2018). In production practice, the quality of baby leaf is sensitive to substrate water content.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plug trays filled with substrate is used for greenhouse baby leaf production with ebb-and-flow (E&F) irrigation systems (Danfeng et al, 2013). E&F irrigation is characterized as producing uniform plants, with a short production cycle, high water-and fertilizer-use efficiency, and adequate plant quality (Yang et al, 2018). In production practice, the quality of baby leaf is sensitive to substrate water content.…”
mentioning
confidence: 99%
“…Few studies have reported the irrigation scheduling strategy for leafy greens by using subirrigation such as E&F irrigation. Irrigation frequency and flood time were identified as two key factors in the E&F irrigation strategy (Yang et al, 2018). In substrate type, flooding depth and time have also been studied to optimize E&F irrigation (Anlauf et al, 2012).…”
mentioning
confidence: 99%